Community Development Planning : Introduction of Integrated Farming System (IFS) to the Rural Community - Yanu Endar Prasetyo; M Ali Mauludin (Jurnal Ilmu Ternak, 2016)
Development Center for Appropriate Technology (DCAT) is a research institute that has a role to develop and implement Appropriate Technology (AT) in accordance with the needs of rural communities in Indonesia. In practice, the application of AT can not be carried out in thescheme of top-down intervention, but rather requires a participatory community developmentmethods. Rural livelihoods, especially in the peasant community, have complex issues, ranging from land tenure, the means of production, waste pollution and management, production capacity, degradation of land, water and irrigation, information of technology, and marketing constraints of agricultural products. Therefore, it is necessary to create community development planning to determine the priority of the AT that is required. This paper will describe the steps of community development planning to introduce the Integrated Farming System (IFS) to the rural community. The setting and case study is the business development group of cattle and rice farmers in Sukatani Village, Subang, West Java, which is expected to be a pioneer of IFS within communities.Keywords : community planning, appropriate technology, integrated farming system, Subang, Indonesia